2015
DOI: 10.1186/s12887-015-0396-6
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of length, weight, and bone mineral density among preterm infants during the first 12 months of corrected age in China

Abstract: BackgroundLimited evidence has been provided on the trajectories of length, weight, and bone mineral density (BMD) among preterm infants in early life in Asian countries.MethodsWe conducted a longitudinal study, which included 652 late preterm (gestational age: 34–36.9 weeks), 486 moderate preterm (32–33.9), 291 very preterm (28–31.9), 149 extremely preterm infants (≤28.9) and 1434 full-term peers (≥37) during the first 12 months of corrected age in Wuhan, China. Weight and length were measured at birth, once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
10
2
1
Order By: Relevance
“…The weight and length of both males and females in preterm infants did not achieve the median measurements of their term peers. Zhao et al [20] found a faster growth rate in preterm infants during the first 12 months of age with the growth rate peaking at 1–3 months of age, but not yet catch up with term infants. Another study from China reported the catch-up growth occurred from 10th and 12th month for weight and length, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…The weight and length of both males and females in preterm infants did not achieve the median measurements of their term peers. Zhao et al [20] found a faster growth rate in preterm infants during the first 12 months of age with the growth rate peaking at 1–3 months of age, but not yet catch up with term infants. Another study from China reported the catch-up growth occurred from 10th and 12th month for weight and length, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…The catch-up growth patterns of preterm infants have been a matter of debate. Zhao et al [4] observed no catch-up growth in weight and length among preterm infants, while Westerberg et al [5] observed that VLBW infants showed significant catch-up growth in both weight and length during the first year of life. Thus, an understanding of the early growth patterns of preterm infants is important and may help improve appropriate daily care practices and reduce the morbidity of growth deviations related to preterm birth.…”
Section: Introductionmentioning
confidence: 99%
“…Por fim, a fase de equilíbrio, caracteriza-se por uma velocidade de crescimento comparável à das crianças saudáveis nascidas a termo (CARDOSO-DEMARTINI; BAGATIN; SILVA; BOGUSZEWSKI, 2011). Cabe destacar que, a intensidade e duração destas fases variam de acordo com a idade gestacional, o peso de nascimento e a gravidade da condição do RN (BOCCA-TJEERTES;VAN BUUREN;BOS;KERSTJENS et al, 2012;LIU;LUO;PENG;XIONG et al, 2019;ZHAO;DING;HU;DAI et al, 2015).Alguns fatores podem influenciar o crescimento pós-natal de prematuros, tais como as intercorrências durante o período de internação e pós-alta hospitalar (ROVER; VIERA; SILVEIRA; GUIMARÃES et al, 2016), as práticas alimentares pós-natais (DAMASCENO; SILVA; XIMENES NETO; FERREIRA et al, 2014) e o estado nutricional ao nascimento (LIMA; CARVALHO; COSTA; MOREIRA, 2014). Durante o perído de internação os principais fatores associados à danos no crescimento do prematuro são as intercorrências clínicas, como infecções, distúbios do trato gastrointestinal e impossibilidade de ingestão alimentar adequada (ALTERMAN, 2016).…”
unclassified